Effect of application of Chlorpropham in sprouting of olluco tubers (Ullucus tuberosus L.) under storage - Aliaga, Isaac (2011)
It was evaluated the effect of Chlorpropham on the sprouting of root’s tubers vegetables (Ullucus tuberosum L.) Tarmeño variety during storage at 15 °C and RH of 85 %, the treatments were 0, 5, 10, 20 and 30 mg of Chlorpropham / kg of tubers, in a completely random design with 4 repetitions. After 60 days of storage the sprouts, length for the control without Chlorpropham was 9.63 cm and for the treatments with Chlorpropham from 0.22 to 0.71 cm after 90 days the length of the sprouts were kept the same and some of them began to dry up, except the control where increased in size from 15 to 20 cm. After 90 days of storage, weight loss for the treatments with Chlorpropham was averaged of 21 % and for the witness of 37.35 %. All Chlorpropham treatments showed a lower number of sprouts per tuber, lower length of buds, fewer number of tubers with sprouts and less weight loss, with a p <0.05, Duncan test showed don’t exist significant differences between treatments with Chlorpropham for the assessed variables, but significant differences with the control treatment.